Active pulmonary targeting against tuberculosis (TB) via triple-encapsulation of Q203, bedaquiline and superparamagnetic iron oxides (SPIOs) in nanoparticle aggregates. (1st January 2019) - Poh, Wilson; Ab Rahman, Nurlilah; Ostrovski, Yan; Sznitman, Josué; Pethe, Kevin; Loo, Say Chye Joachim
Abstract: Tuberculosis (TB) has gained attention over the past few decades by becoming one of the top ten leading causes of death worldwide. This infectious disease of the lungs is orally treated with a medicinal armamentarium. However, this route of administration passes through the body's first-pass metabolism which reduces the drugs' bioavailability and toxicates the liver and kidneys. Inhalation therapy represents an alternative to the oral route, but low deposition efficiencies of delivery devices such as nebulizers and dry powder inhalers render it challenging as a favorable therapy. It was hypothesized that by encapsulating two potent TB-agents, i.e. Q203 and bedaquiline, that inhibit the oxidative phosphorylation of the bacteria together with a magnetic targeting component, superparamagnetic iron oxides, into a poly (D, L-lactide-co-glycolide) (PDLG) carrier using a single emulsion technique, the treatment of TB can be a better therapeutic alternative. This simple fabrication method achieved a homogenous distribution of 500 nm particles with a magnetic saturation of 28 emu/g. Such particles were shown to be magnetically susceptible in an in-vitro assessment, viable against A549 epithelial cells, and were able to reduce two log bacteria counts of the Bacillus Calmette-Guerin (BCG) organism. Furthermore, through the use of an external magnet, our in-silico Computational Fluid Dynamics (CFD) simulations support the notion of yielding 100% deposition in the deep lungs. Our proposed inhalation therapy circumvents challenges related to oral and respiratory treatments and embodies a highly favorable new treatment regime.